Heart failure in congenital heart disease from fetus to adult - Shaddy, Robert E. (Springer, 2011)
This book will provide both an evidence base and practical recommendations for the treatment of patients with congenital heart disease. It will be a resource to all health care providers, including pediatric cardiologists, pediatric intensivists, pediatric heart surgeons, fetal specialists, maternal fetal medicine specialists, neonatologists, nurses, advanced practice nurses, in addition to trainees in the field. It will summarize world knowledge on the topic of heart failure in patients with congenital heart disease. It will provide an in depth analysis of the current methods of diagnosis and.